Exploring the role of Peanut (Arachis hypogaea L.) root architecture in enhancing adaptation to climate change for sustainable agriculture and resilient crop production: A review - Yohannes Gelaye; Jihua Li; Huaiyong Luo (Journal of Genetic Engineering and Biotechnology, 2025)
Peanut (Arachis hypogaea L.) cultivation is increasingly vulnerable to climate change, with drought and heat stress emerging as major constraints to productivity and food security. This review explores the critical role of root architecture in enhancing peanut adaptation to environmental stressors, and evaluates current strategies and future directions for improving root traits through genetic, physiological, and agronomic approaches. Efficient root systems, characterized by deeper rooting and optimized xylem design, significantly improve water and nutrient acquisition under drought conditions. Key regulators such as abscisic acid (ABA), strigolactones, and specific root-related genes modulate root development and stress responses. Root exudates further enhance soil root interactions, while the peanut root microbiome contributes to nutrient cycling and resilience. Biotechnological tools, including quantitative trait loci (QTL) mapping and CRISPR/Cas-based genome editing, are being harnessed to manipulate root traits at the molecular level. Agronomic practices like mulching and cover cropping synergize with genetic improvements by enhancing soil structure and moisture retention. Strengthening peanut root architecture through the integration of modern breeding, biotechnological advances, and sustainable soil management offers a promising path toward climate-resilient peanut production. Future research should prioritize the convergence of these approaches, alongside microbiome exploration, to secure yield stability and food security in a changing climate.